I'll sleep when I'm dead the dirty life and times of Warren Zevon - Zevon, Crystal (Ecco, 2007)
When Warren Zevon died in 2003, he left behind both a fanatical cult following and a rich catalog of dark, witty rock-n-roll classics that includes "Lawyers, Guns, and Money," "Excitable Boy," and the immortal "Werewolves of London." He also left a trove of misadventures and anecdotes, a veritable rock opera of drugs, women, celebrity, high times, and hard ways. As Warren once said, "I got to be Jim Morrison a lot longer than he did." This book is an intimate and unusual oral history of one of our most original and distinctive rock-and-roll antiheroes. Narrated by his former wife and longtime co-conspirator, Crystal Zevon, it book draws on over eighty interviews with the likes of Bruce Springsteen, Stephen King, Billy Bob Thornton, Jackson Browne, Bonnie Raitt, and countless others who came under his mischievous spell. The result is a raucous and moving tale of love and obsession, creative genius and epic bad behavior.--From publisher description.